Multiplicity and simultaneity in ethnographic research: Exploring the use of drones in Ghana. Issue 480 (17th July 2021) - Adotey, Edem
Abstract: This research note explores the ethical and methodological implications of using drones for ethnographic research at events that involve simultaneous activities and/or large crowds and large spaces. Based on the methodological challenges of collecting visual data using cameras in the case of royal funerals in Ghana, this note argues that the aerial viewpoint provided by drones could transform visual data collection by capturing sophisticated views of multiple events happening at the same time. However, it also identifies ethical and methodological challenges of using drones and argues that it could obscure the understanding of sociocultural complexities. This research note contributes to our understanding of visual methodologies by highlighting how drone technology extends and complicates current understandings and debates on the use of photographs and films in ethnography.